Striking a delicate balance: ethical considerations and promising advances in timely diagnosis and patient safety for Hunter syndrome - Sadiq, Najia; Ahmed, Osaid; Ubaid, Fareeha (Journal of the Pakistan Medical Association, 2025)
Hunter syndrome (HS) is a rare X-linked lysosomal storage disease that poses a significant challenge to affected individuals and healthcare professionals. HS is characterised by MRI scans that often show extensive white matter changes as well as dilated perivascular spaces, despite apparently normal intellectual skills. HS requires early diagnosis to initiate enzyme replacement therapy and potential improvements in patients’ outcomes. However, using intrusive methods to diagnose patients has serious ethical problems. Seeking early diagnosis and effective treatment for HS necessitates a careful balancing act among the advancement of medical research, the prioritisation of patient safety, comfort, and resolving moral dilemmas. We can give these individuals hope and improved outcomes by creating non-invasive biomarkers, improving upon existing diagnostic methods, and looking into novel treatment approaches. Programmes that prioritise early identification and screening in underserved areas, raise awareness and ensure equitable treatment for all HS-affected individuals can also help close the gap. Keywords: Biomarkers, Hunter’s syndrome, Mucopolysaccharidosis II, Enzyme Replacement Therapies, Ethical Issues.